Long-term observational approach in women with histological diagnosis of cervical low-grade squamous intraepithelial lesion: an Italian multicentric retrospective cohort study. Issue 7 (3rd July 2019) - Ciavattini, Andrea; Serri, Matteo; Di Giuseppe, Jacopo; Liverani, Carlo Antonio; Gardella, Barbara; Papiccio, Maria; Delli Carpini, Giovanni; Morini, Stefano; Clemente, Nicolò; Sopracordevole, Francesco
Abstract : Objective: To evaluate the risk of progression to high-grade squamous intraepithelial lesion (HSIL) (CIN2-3) or invasive cancer in women with histopathological diagnosis of low-grade squamous intraepithelial lesion (LSIL) (CIN1), managed in a long-term observational approach up to 5 years. Design: Retrospective cohort study. Setting: Four tertiary referral hospital. Participants: 434 women with adequate colposcopy and complete colposcopic charts were included in the present analysis. Women with glandular lesions on the referral cytology or previous diagnosis of cervical dysplasia or invasive cervical cancer or with synchronous vaginal, or with HIV infection or immunodepression were excluded. Primary and secondary outcome measures: The main study outcome was the rate of progression to histopathological HSIL (CIN2-3) or invasive cancer at any time during 5 years of follow-up. The possible risk factors were also evaluated. As secondary outcome, we analysed the possible risk factors at the 24-month evaluation for histopathological HSIL (CIN2-3) or invasive cancer progression between 2 and 5 years from initial diagnosis. Results: A progression to histopathological HSIL (CIN2-3) was found in a total of 32 (7.4%) cases during 5 years of follow-up. A histopathological diagnosis of HSIL (CIN3) was found in four patients (0.9%) and no case of invasive cancer was detected. High-grade cytology at inclusion and the presence of a positive high-risk human papillomavirus (HR-HPV) DNA test at 2 years from inclusion maintained a significant correlation with the risk of histopathological progression to HSIL (CIN2-3). Conclusions: The results of our study showed a low rate (7.4%) of histopathological progression to HSIL (CIN2-3) in women with LSIL (CIN1) diagnosis during long-term follow-up up to 5 years. In case of positive HR-HPV DNA test at the 2 years evaluation an excisional treatment could be the preferred choice to prevent progression to HSIL (CIN2-3) in the following years, preferring a continuation of follow-up in case of HR-HPV DNA negative result.